Oxygen and Glucose Deprivation Induces Bergmann Glia Membrane Depolarization and Ca2+ Rises Mainly Mediated by K+ and ATP Increases in the Extracellular Space - Helleringer, Romain; Chever, Oana; Daniel, Hervé; Galante, Micaela (Frontiers in Cellular Neuroscience, 2017)
During brain ischemia, intense energy deficiency induces a complex succession of events including pump failure, acidosis and exacerbated glutamate release. In the cerebellum, glutamate is the principal mediator of Purkinje neuron anoxic depolarisation during episodes of oxygen and glucose deprivation (OGD). Here, the impact of OGD is studied in Bergmann glia, specialized astrocytes closely associated to Purkinje neurons. Patch clamp experiments reveal that during OGD Bergmann glial cells develop a large depolarising current that is not mediated by glutamate and purinergic receptors but is mainly due to the accumulation of K+ in the extracellular space. Furthermore, we also found that increases in the intracellular Ca2+ concentration appear in Bergmann glia processes several minutes following OGD. These elevations require, in an early phase, Ca2+ mobilization from internal stores via P2Y receptor activation, and, over longer periods, Ca2+ entry through store-operated calcium channels. Our results suggest that increases of K+ and ATP concentrations in the extracellular space are primordial mediators of the OGD effects on Bergmann glia. In the cerebellum, glial responses to energy deprivation-triggering events are therefore highly likely to follow largely distinct rules from those of their neuronal counterparts.